Validitas VALIDITAS HANDOUT ELEKTRONIK BERBASIS PROJEK PENGUATAN PROFIL PELAJAR PANCASILA TEMA KEWIRAUSAHAAN - Dea Stivani Suherman; Annisa Fadhilaturrahmi; Desnita; Hidayati (JURNAL FIRNAS, 2025)
Learning in the Merdeka curriculum consists of intracurricular, co-curricular, and extracurricular learning. Co-curricular learning is at least in the form of a project to strengthen the profile of Pancasila students. This research aims to develop and test the validity of electronic handouts based on the Pancasila Student Profile Strengthening Project (P5) with the theme of entrepreneurship. This product is designed to support the implementation of the Independent Curriculum by integrating Pancasila values and entrepreneurial principles in learning. The research method uses ADDIE development, design. This article presents the results of expert validation tests. Validation by three experts using a questionnaire instrument consisted of 7 aspects which were described into 89 items. Data were analyzed using the Aiken's V. validity index of assessment categories using the Likert scale. The validation results showed that the electronic handout met the valid criteria with an average score of 0.93, including aspects of content feasibility (0.89), presentation (0.92), language (0.88), visual display (0.91), strengthening the Pancasila Student Profile (0.96), and entrepreneurship theme (0.99). These findings indicate that the product being developed, conceptually. This handout can be tested in the real field by both teachers and students.